Genotypic and Environmental Variations in Kernel Color Indices in the Main Almond (Prunus dulcis (Mill.) D.A. Webb) Cultivars Grown in North-Eastern Morocco - El Hassan Sakar; Mohamed El Yamani; Abdelali Boussakouran; Yahia Rharrabti (Scientifica)
Color indices are important quality traits that define the consumer visual acceptance and agroindustrial preferences. Little is known regarding these properties in the commercial almond cultivars grown in Morocco. This work aimed at investigating kernel color indices in five cultivars, namely, “Fournat de Brézenaud,” “Tuono,” “Ferragnès,” “Ferraduel,” and “Marcona.” Color indices consisted in the following: brightness (L∗), redness index (a∗), yellowness index (b∗), chroma (C∗), hue (H∗), and metric saturation (S∗). Measurements were performed over three consecutive growing seasons (2016–2018) across five different sites from northern (Aknoul, Bni Hadifa, and Tahar Souk) and eastern (Rislane and Sidi Bouhria) Morocco. All factors (cultivar, growing season, and site) affected significantly studied color properties; however, genotype was the main variability source. Wide variabilities were found among cultivars. “Marcona” showed the highest L∗, while “Ferragnès” and “Ferraduel” displayed greater scores of a∗, b∗, C∗, and S∗. Sidi Bouhria presented the lowest L∗ but higher a∗, H∗, and S∗. Moreover, Bni Hadifa displayed higher L∗, b∗, and C∗. 2016 (drier growing season) had the highest values of most indices. Principal component analyses (PCA) discriminate all factors through the first three components: PC1 (61%, genetic component) and PC2 (30%) and PC3 (7%) which were of environmental nature since they separate sites and growing seasons, respectively. Despite environmental effects, we suggested a possible discrimination among the studied cultivars based on their kernel color indices. Drought conditions during fruit development seemed to improve kernel quality via synthesis of pigments resulting in higher a∗ and b∗.